Perceived ease of activity (but not strategy use) mediates the relationship between self-efficacy and activity engagement in midlife and older adults. (3rd October 2019) - Curtis, Rachel G.; Windsor, Tim D.
Abstract: Objectives: Activity participation is associated with a range of positive outcomes in older adults but tends to decline with age. Understanding protective factors is important to facilitate activity in later life. Social cognitive theory suggests that having high self-efficacy may promote activity because individuals with higher self-efficacy perceived their activities to be easier and use adaptive strategies to overcome barriers to activity. Despite considerable research linking self-efficacy and activity, limited research has examined the proposed mechanisms behind this association. This study therefore examined whether perceived ease of activity and use of adaptive strategies account for the association between self-efficacy and activity. Method: Participants were 412 adults aged 50–93 years who completed a cross-sectional survey. Structural equation modelling was used to examine whether the effects of self-efficacy on activity were mediated by perceived ease of activity and use of adaptive strategies. Results: Perceived ease of activity mediated the positive associations between self-efficacy and social (0.04 [0.02, 0.07]) and physical activity (0.16 [0.08, 0.25]), but not mental activity (0.01 [0.000, 0.03]). For physical activity, this effect was stronger for adults aged 70+ years than those aged 50–69 years (older a 2 * b 2 - younger a 2 * b 2 0.13 [0.04, 0.24]). Use of adaptive strategies was not a significant mediator in any model. Conclusion: This study suggests that self-efficacy may influence older adults' perception of activities and, in turn, the activities they choose to participate in. This has potential implications for the development of interventions aimed at promoting activity engagement in later life.